Comportamento de algumas variedades de feijão na zona da mata, Minas Gerais - Vieira, Clibas (Revista Ceres, 2025)
This paper describes the performance of 8 dry bean (Phaseolus vulgaris L.) varieties grown in the Zona da Mata area of Minas Gerais. These varieties have shown superior yielding ability in the Federal University of Viçosa bean research program. "Rico 23" (black), 'Manteigio Fosco 11' (large, buff), 'Ri- copardo 896' (brown), 'Ricobaio 1014' (buff), and 'Cost Rica’ (black) are now recommended for commercial production. The variety 'Manteigdo Fosco 11' has been the best of its type and is therefore recommended despite serious weaknesses. Several bean varieties of each type are planted in the Zona da Mata area. This genetic diversity should be maintained to insure against serious disease epidemics.